Temperature and SAR distribution in human head from mobile phone of 2G, 3G, 4G using FEM modeling - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
In this study, to examine the impact of distance, and angle on the human head during the regular functioning of a mobile phone, a head model is constructed via COMSOL software dataset. The handset antenna has been configured with a patch antenna being a radiation source at 900 MHz, 1800 MHz and 2100MHz, respectively. Temperature increase and specific absorption rate distribution on the user's head with various angles and distances are simulated by using finite element method. It is observed that the values that are obtained in the simulations are in good agreement with the basic limitations set up ICNIRP, designating that the safety restrictions will not be dared by the usage of user. © 2017 IEEE.
Keywords: finite element method; human head; specific absorption rate